A novel human biomonitoring study by semiconductor gas sensors in Exposomics: investigation of health risk in contaminated sites. (1st July 2022) - Longo, Valentina; Forleo, Angiola; Radogna, Antonio Vincenzo; Siciliano, Pietro; Notari, Tiziana; Pappalardo, Sebastiana; Piscopo, Marina; Montano, Luigi; Capone, Simonetta
Abstract: Two areas in central-southern Italy Land of Fires in Campania and Valley of Sacco river in Lazio are known to be contaminated sites, the first due to illegal fly-tipping and toxic fires, and the second due to an intensive industrial exploitation done by no-scruple companies and crooked public administration offices with dramatic consequences for environment and resident people. The work is intended to contribute to Human BioMonitoring (HBM) studies conducted in these areas on healthy young male population by a semiconductor gas sensor array trained by SPME-GC/MS. Human semen, blood and urine were investigated. The fingerprinting of the Volatile Organic Compounds (VOCs) by a gas sensors system allowed to discriminate the different contamination of the two areas and was able to predict the chemical concentration of several VOCs identified by GC/MS. Graphical abstract: Image 1 Highlights: Living in contaminated sites is recognized to be a health risk. Human biomonitoring study was carried out on residential risk sample population. Analysis of VOCs in human biofluids fingerprints population in contaminated sites. Advanced semiconductor gas sensors can be used in Human Biomonitoring. GC/MS and gas sensors are complementary tools for profiling VOCs in body matrices.